Book Review: Lyons, Daniel Jack (2022) Like a River. Loose Joints (Alternautas, 2023)
This review discusses a few critical aspects of representing queer individuals from the Amazon forest in the wake of Lyons' book of photographic essays. It is argued that from a scenario of under-representation, the book represents a positive step to enlighten threatened communities, even if as an intermediary step towards native forms of representation and liberation.